2014
DOI: 10.2139/ssrn.2496174
|View full text |Cite
|
Sign up to set email alerts
|

Capital Structure and Corporate Performance: Evidence from Jordan

Abstract: This study is to investigate the effect which capital structure has had on corporate performance using a panel data sample representing of 167 Jordanian companies during 1989-2003. Our results showed that a firm's capital structure had a significantly negative impact on the firm's performance measures, in both the accounting and market's measures. We also found that the short-term debt to total assets (STDTA) level has a significantly positive effect on the market performance measure (Tobin's Q). The Gulf Cris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
89
3
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(120 citation statements)
references
References 35 publications
23
89
3
5
Order By: Relevance
“…The hypothesis that a company's capital structure should have a negative impact on its performance is confirmed. The results of this hypothesis are consistent with the research results of Onaolapo and Kajola's (2010), Fosberg and Ghosh's (2006), Houang and Song's (2006), Mramor and Crnigoj's (2009) and Zeitun and Tian's (2007) work. Company growth opportunities show a positive and statistically significant relationship with ROA at the 10% level.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The hypothesis that a company's capital structure should have a negative impact on its performance is confirmed. The results of this hypothesis are consistent with the research results of Onaolapo and Kajola's (2010), Fosberg and Ghosh's (2006), Houang and Song's (2006), Mramor and Crnigoj's (2009) and Zeitun and Tian's (2007) work. Company growth opportunities show a positive and statistically significant relationship with ROA at the 10% level.…”
Section: Resultssupporting
confidence: 91%
“…Company growth opportunities show a positive and statistically significant relationship with ROA at the 10% level. The results of this hypothesis are not consistent with the results obtained from the researches of Zeitun and Tian (2007) and Onaolapo and Kajola (2010). Size of the company, age, quick ratio and asset structure did not show any significant relationship with ROA.…”
Section: Resultscontrasting
confidence: 79%
See 1 more Smart Citation
“…Bu bulgular daha önce Türkiye'de ve gelişmekte olan ülkelerde firma performansı ve firma değeri üzerinde yapılan bazı çalışmalarda elde edilen bulgularla benzerlik göstermektedir (Mukherji, Dhatt, & Kim, 1997;Demir, 2001;Zeitun & Tian, 2007;Birgili & Düzer, 2010;Pratheepkanth, 2011;Ahmad, Abdullah & Roslan, 2012;Yener & Karakuş, 2012;Ayrıçay & Türk, 2014). Bahse konu çalışmalar, bu çalışmada olduğu gibi sermaye yapısı ile firma performansı ve değeri arasında negatif bir ilişki olduğu sonucuna varmışlardır.…”
Section: Bulgularunclassified
“…A few of them take the macro-economic environment into account and integrate internal and external factors to give an overall consideration of the influence factors on enterprise development. For instance, Demsetz [4] suggested that different external environment lead to different equity financing structures of enterprises; in the study on the relationship between financing structure and financial performance, RamiZeitun et al [5] found that the financing structures of 167 Jordanian companies were significantly negatively correlated to their financial performances, and the companies' business performances were affected by the macro-environment. As for domestic scholars, Sun Linjie and Sun Linzhao [6] carried out the analytic hierarchy process and found that the R&D ability, financial status and other factors are the primary influence factors on enterprise's financing capacity.…”
Section: Introductionmentioning
confidence: 99%